Critical intersections in contemporary curriculum & pedagogy - Jewett, Laura M.; Calderon-Berumen, Freyca; Espinosa-Dulanto, Miryam (Emerald Publishing Limited : Information Age Publishing, Inc., 2018)
"This volume offers a collection of scholarship that extends curricular conversations, crosses borders of praxis, and expands democratic, critical and aesthetic imaginaries- toward the ends of lending momentum to the ever-present and wide-open question: What is to be done-- in terms of curriculum and pedagogy-- in p-12 schools, in teacher education and other higher education contexts, in communities, as well as within our own lives as teachers, leaders and learners? These chapters represent perspectives from curriculum workers/teachers/scholars/activists across theoretical landscapes and spanning a diversity of positionalities within critical intersections of power and privilege as they relate to identity, culture and curriculum as well as to social justice, schools and society"-- Provided by publisher.
Keywords: Culturally relevant pedagogy.; Education -- Curricula.; Education -- Social aspects.; Curriculum planning and development.; elektronické knihy; electronic books